Low-moisture high-safety lithium battery diaphragm and preparation method thereof

Modifying the gamma-phase ultrafine porous alumina by silane coupling agent reduces the water content of the lithium battery separator, solving the problem of high diaphragm water content, achieving a low moisture, high safety and high performance separator, and improving the overall performance of the lithium battery.

CN119651050APending Publication Date: 2025-03-18HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411695306.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The water content of existing lithium battery separators is relatively high, which affects performance, especially in high humidity environments.

Method used

The surface modification of the gamma-phase ultrafine porous alumina is formed by surface modification of the gamma-phase ultrafine porous alumina by using a silane coupling agent, which reduces the water content of the separator while maintaining high ionic conductivity and excellent wetting.

Benefits of technology

It realizes a low moisture, high safety and high performance lithium battery separator, improves the liquid absorption and liquid retention ability of the separator, reduces the internal resistance of the lithium battery, and improves the power density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119651050A_ABST
    Figure CN119651050A_ABST
Patent Text Reader

Abstract

The invention discloses a low-moisture and high-safety lithium battery diaphragm and a preparation method thereof.The low-moisture and high-safety lithium battery diaphragm comprises a base membrane and a coating on the base membrane, the coating comprises modified gamma-phase superfine porous aluminum oxide, the modified gamma-phase superfine porous aluminum oxide is obtained by modifying gamma-phase superfine porous aluminum oxide through a silane coupling agent, and the modified gamma-phase superfine porous aluminum oxide is prepared from modified gamma-phase superfine porous aluminum oxide. The silane coupling agent is one of a vinyl silane coupling agent and a methyl silane coupling agent. According to the invention, surface modification is carried out on gamma-phase superfine porous alumina by using a silane coupling agent with a hydrophobic group, so that the diaphragm has high ionic conductivity, good high temperature resistance and good liquid absorption and retention capability, and meanwhile, the water content of the diaphragm is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a low-moisture and high-safety lithium battery separator and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are developing towards high energy density, high power density and long life to meet the growing market demand and application requirements. In this process, the diaphragm, as a key component of the battery, is also evolving towards a thinner and more functional direction to improve the overall performance and safety of the battery. The diaphragm is not only an indispensable part of the battery, but also plays a vital role in the operation of the battery. Its main functions include effectively absorbing and storing electrolyte to ensure good contact between the electrolyte and the electrode, thereby improving the ion conduction efficiency. In addition, the diaphragm must also have excellent thermal stability to prevent the occurrence of thermal shrinkage and ensure the safe operation of the battery under high temperature conditions.

[0003] During the sintering process of alumina, when AlOOH transforms to the γ phase, water molecules will escape in the form of gas to form pores, thereby generating γ-phase ultrafine porous alumina with highly porous characteristics. This porous alumina has an extremely rich pore structure, which can effectively reduce the overall weight of the coating film, making the diaphragm thinner and lighter, while being able to better carry the infiltration and absorption of the electrolyte, thereby significantly improving the liquid absorption and retention rate and ion conductivity of the diaphragm. The good density of the coating allows the coating film to maintain a stable structure under high temperature conditions. This not only helps to improve the overall performance of the battery, but also extends its service life.

[0004] However, due to the rich pore structure of γ-phase ultrafine porous alumina, its specific surface area is significantly increased. Therefore, in some cases, the water content of this porous alumina coated diaphragm is often high. This phenomenon may affect the performance of the diaphragm, especially in high humidity environments. Therefore, how to effectively reduce the water content of porous alumina coated diaphragms has become a key issue that needs to be solved urgently. To address this issue, researchers can explore a variety of strategies, such as optimizing the sintering process, adjusting the material formulation, and introducing hydrophilic or hydrophobic additives to achieve effective control of moisture, thereby improving the performance and stability of the diaphragm. This will open up new directions for the research and development of high-performance batteries and diaphragm materials in the future. Summary of the invention

[0005] In view of the deficiencies of the prior art, an object of the present invention is to provide a low-moisture and high-safety lithium battery separator.

[0006] Another object of the present invention is to provide a method for preparing a low-moisture and high-safety lithium battery separator.

[0007] Another object of the present invention is to provide a slurry.

[0008] Another object of the present invention is to provide a method for preparing the slurry.

[0009] The purpose of the present invention is achieved through the following technical solutions.

[0010] A low-moisture and high-safety lithium battery separator comprises: a base film and a coating on the base film, wherein the coating comprises: modified γ-phase ultrafine porous alumina, wherein the modified γ-phase ultrafine porous alumina is obtained by modifying the γ-phase ultrafine porous alumina with a silane coupling agent, wherein the silane coupling agent is one of a vinyl silane coupling agent and a methyl silane coupling agent.

[0011] In the above technical scheme, the method for obtaining modified γ-phase ultrafine porous alumina is: mix γ-phase ultrafine porous alumina, water and silane coupling agent until uniform, dry and grind to obtain the modified γ-phase ultrafine porous alumina, wherein the ratio of γ-phase ultrafine porous alumina, water and silane coupling agent is (35-40): (50-70): (0.1-0.3) by mass.

[0012] In the above technical solution, the particle size of the modified γ phase ultrafine porous alumina is D50=0.52-0.63 μm, D90=1.252-1.465 μm, and the porosity of the modified γ phase ultrafine porous alumina is 20-40%.

[0013] The method for preparing the above-mentioned low-moisture and high-safety lithium battery separator comprises: coating the slurry on the base film, drying, obtaining a coating on the base film, and obtaining the low-moisture and high-safety lithium battery separator, wherein the slurry comprises: water, modified γ-phase ultrafine porous alumina, an adhesive and a dispersant.

[0014] In the above technical solution, the adhesive is an acrylate copolymer solution, and the concentration of the acrylate copolymer in the acrylate copolymer solution is 15-25wt%.

[0015] In the above technical solution, the dispersant is ammonium polyacrylate.

[0016] In the above technical solution, the coating thickness is 2 to 3 μm.

[0017] In the above technical solution, the coating speed is 20 to 40 m / min.

[0018] A slurry comprises: water, modified gamma phase ultrafine porous alumina, adhesive and dispersant, wherein the ratio of water, modified gamma phase ultrafine porous alumina, adhesive and dispersant is (50-70): (25-35): (5-8): (0.2-0.5) by weight.

[0019] In the above technical solution, the ratio of water, modified γ-phase ultrafine porous alumina, adhesive and dispersant is preferably (50-70): (31-35): (5-8): (0.2-0.5) by mass.

[0020] In the above technical solution, the particle size of the slurry is D50: 0.440-0.515 microns, D90: 0.868-1.112 microns.

[0021] The preparation method of the above-mentioned slurry comprises: mixing water, modified γ-phase ultrafine porous alumina, adhesive and dispersant until uniform to obtain slurry, wherein the ratio of water, modified γ-phase ultrafine porous alumina, adhesive and dispersant is (50-70): (25-35): (5-8): (0.2-0.5) by mass.

[0022] In the above technical solution, the method for preparing the slurry comprises the following steps:

[0023] Step 1, mixing a dispersant, water and modified γ-phase ultrafine porous alumina until uniform to obtain a first solution;

[0024] In step 1, a dispersant, water and modified γ-phase ultrafine porous alumina are mixed, and stirred at a rotation speed of 3000-4000 r / min and a revolution speed of 50-70 r / min for 20-25 min until the mixture is uniform, to obtain a first solution.

[0025] Step 2: Mix the first solution and the adhesive until they are uniform to obtain a slurry.

[0026] In step 2, the first solution and the adhesive are mixed, and stirred and ultrasonicated for 20 to 30 minutes in a vacuum environment until they are uniform. The vacuum degree of the vacuum environment is 0.06 to 0.08 KPA, the stirring rotation speed is 2000 to 3000 r / min, the revolution speed is 30 to 40 r / min, and the ultrasonic frequency is 5 to 8 kHz.

[0027] Application of silane coupling agent modified γ-phase ultrafine porous alumina in reducing the water content of diaphragms.

[0028] Application of silane coupling agent modified γ-phase ultrafine porous alumina in improving the ionic conductivity of membranes.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The present invention uses a silane coupling agent with a hydrophobic group to perform surface modification on the γ-phase ultrafine porous alumina, so that a very small amount of hydrophobic groups are grafted onto the surface of the γ-phase ultrafine porous alumina, thereby reducing the water content of the diaphragm (a diaphragm with a lower water content is an important way to improve the safety and cycle stability of lithium batteries), and the γ-phase ultrafine porous alumina has a rich pore structure, which not only reduces the weight of the diaphragm, but also enables the diaphragm to maintain high ionic conductivity and excellent wettability. The γ-phase ultrafine porous alumina makes the coating have good compactness and gives the diaphragm good high temperature resistance.

[0031] 2. The rich pore structure of γ-phase ultrafine porous alumina (particles) can not only reduce the weight of the diaphragm but also enhance the absorption of electrolyte, so that the diaphragm can store more electrolyte and shorten the lithium ion (Li + ) migration path, thereby improving the liquid absorption and retention capacity and ionic conductivity of the separator, reducing the internal resistance of the lithium battery, and thus improving the power density.

[0032] 3. The silane coupling agent hydrolyzes to form Si-OH under a certain pH environment, and the adjacent Si-OH condenses into Si-O-Si. At the same time, Si-OH forms hydrogen bonds with -OH on the surface of the γ-phase ultrafine porous alumina particles, thereby bonding to the surface of the γ-phase ultrafine porous alumina (particles). BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the SEM image of the diaphragm prepared in Example 4. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0035] The raw material information involved in the following examples is as follows:

[0036] γ-phase ultrafine porous alumina (powder): Shanghai Baitu New Materials Technology Co., Ltd.;

[0037] Acrylate copolymer solution: Baoding Lucky Imaging Material Technology Co., Ltd.;

[0038] Ammonium polyacrylate: Shanghai Sunray Polymer Materials Technology Co., Ltd.;

[0039] In the following examples, water is pure water.

[0040] In the following embodiments, the base film is a PE film, and the thickness of the base film is 7 microns.

[0041] Ionic conductivity: The test temperature is 25°C and the test relative humidity is 55-60%.

[0042] Examples 1 to 3

[0043] A method for preparing a slurry, the slurry comprising the following steps:

[0044] Step 1, mixing a dispersant, water and modified γ-phase ultrafine porous alumina in a double planetary mixer, stirring for B (min) at a rotation speed of A1 (r / min) and a revolution speed of A2 (r / min) until uniform, to obtain a first solution, wherein the dispersant is ammonium polyacrylate;

[0045] Step 2, mixing the first solution and the adhesive in a double planetary mixer, stirring and ultrasonic (high-speed dispersion) for 20 minutes in a vacuum environment with an ultrasonic oscillation function until uniform, to obtain a slurry, wherein the ratio of water, modified γ-phase ultrafine porous alumina, adhesive and dispersant is X by mass, wherein the vacuum degree of the vacuum environment is C (KPA), the stirring rotation speed is 3000r / min, the revolution speed is 40r / min, the ultrasonic frequency is D (kHz), the adhesive is an acrylate copolymer solution (acrylate copolymer is polymerized by acrylic acid and acrylamide), and the concentration of acrylate copolymer in the acrylate copolymer solution is 20wt%.

[0046] The method for obtaining the modified γ-phase ultrafine porous alumina is as follows: γ-phase ultrafine porous alumina (D50: 0.478 μm, D90: 1.213 μm), water and silane coupling agent are mixed in a double planetary mixer, stirred at a rotation speed of 1500 r / min and a revolution speed of 50 r / min for 40 min until uniform, dried in a 60°C oven for 1 h, and ground to obtain a modified γ-phase ultrafine porous alumina with a particle size of D50=0.601 μm and D90=1.321 μm (porosity of 39.8%). In terms of mass fraction, the ratio of water to silane coupling agent in the method for obtaining the modified γ-phase ultrafine porous alumina is Y, and the silane coupling agent is vinyl triethoxysilane. The porosity of the γ-phase ultrafine porous alumina and the modified γ-phase ultrafine porous alumina is basically the same. A1, A2, B, C, D, X, and Y are shown in Table 1.

[0047] Table 1

[0048]

[0049]

[0050] The particle size of the slurry prepared in Example 1 is D50: 0.495 microns, D90: 0.973 microns; the particle size of the slurry prepared in Example 2 is D50: 0.501 microns, D90: 1.012 microns; the particle size of the slurry prepared in Example 3 is D50: 0.486 microns, D90: 0.993 microns.

[0051] Comparative Example 1

[0052] A method for preparing a slurry comprises: stirring γ-phase alumina, water and a dispersant at high speed for 30 minutes in a double planetary mixer (rotation speed is 3000 r / min, revolution speed is 50 r / min), then ultrasonicating at a frequency of 5 kHz for 15 minutes, adding an adhesive and stirring and ultrasonically oscillating for 25 minutes in a vacuum environment with an ultrasonic oscillation function (stirring rotation speed is 3000 r / min, revolution speed is 40 r / min, and ultrasonic frequency of ultrasonic oscillation is 5 kHz) to obtain a slurry, wherein the adhesive is an acrylate copolymer solution (acrylate copolymer is polymerized from acrylic acid and acrylamide), the concentration of the acrylate copolymer in the acrylate copolymer solution is 20wt%, the dispersant is ammonium polyacrylate, the particle size of the γ-phase alumina is D50: 0.825 micron, D90: 1.933 micron, and the ratio of the γ-phase alumina, water, dispersant and adhesive is 25:63.5:0.5:6 in terms of mass fraction.

[0053] Comparative Example 2

[0054] A method for preparing a slurry comprises: mixing a silane coupling agent, a γ-phase ultrafine porous alumina (D50: 0.478 μm, D90: 1.213 μm), water, a dispersant and an adhesive, and simultaneously stirring and ultrasonicating for 30 minutes in a double planetary mixer (the stirring rotation speed is 3000 r / min, the revolution speed is 50 r / min, and the ultrasonic frequency of the ultrasonication is 5 kHz) until uniform, to obtain a slurry, wherein the ratio of the silane coupling agent, the γ-phase ultrafine porous alumina, water, the dispersant and the adhesive is 0.2:25:66.2:0.5:8 by mass. The dispersant, the silane coupling agent and the adhesive are the same as those in Example 1.

[0055] Comparative Example 3

[0056] A method for preparing a slurry is basically the same as that of Example 1, except that "modified γ-phase ultrafine porous alumina" is replaced by "modified α-phase ultrafine alumina".

[0057] The method for obtaining "modified α phase ultrafine alumina" is basically the same as the method for obtaining modified γ phase ultrafine porous alumina in Example 1, the only difference is that "γ phase ultrafine porous alumina" is replaced by "α phase ultrafine alumina". The particle size of α phase ultrafine alumina is D50 = 0.599 μm, D90 = 1.289 μm.

[0058] Examples 4 to 6 and Comparative Examples 4 to 6

[0059] A method for preparing a diaphragm comprises: placing a base film on a coating machine filled with slurry for single-sided coating (coating speed is E (m / min)), pulling it into a drying device through a traction roller and drying it at 50°C for 2 minutes, obtaining a coating on the base film, and obtaining a diaphragm, wherein the slurry is one of the slurries prepared in Examples 1 to 3 and Comparative Examples 1 to 3, and the diaphragm prepared in Examples 1 to 3 is a low-moisture and high-safety lithium battery diaphragm.

[0060] Table 2

[0061] Diaphragm Slurry for preparing diaphragm E(m / min) Example 4 Example 1 30 Example 5 Example 2 40 Example 6 Example 3 30 Comparative Example 4 Comparative Example 1 30 Comparative Example 5 Comparative Example 2 30 Comparative Example 6 Comparative Example 3 30

[0062] Example 4 Test parameters of the prepared diaphragm:

[0063]

[0064] Example 5 Test parameters of the prepared diaphragm:

[0065]

[0066]

[0067] Example 6 Test parameters of the prepared diaphragm:

[0068]

[0069] Test parameters of the diaphragm prepared in Comparative Example 4:

[0070]

[0071]

[0072] Test parameters of the diaphragm prepared in Comparative Example 5:

[0073]

[0074] Test parameters of the diaphragm prepared in Comparative Example 6:

[0075]

[0076]

[0077] Figure 1 This is an electron microscope image of the diaphragm prepared in Example 4.

[0078] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A low-moisture and high-safety lithium battery separator, characterized in that: include: The base film and the coating on the base film include: modified gamma-phase ultrafine porous alumina, which is obtained by modifying the gamma-phase ultrafine porous alumina with a silane coupling agent, and the silane coupling agent is one of a vinyl silane coupling agent and a methyl silane coupling agent.

2. The low-moisture and high-safety lithium battery separator according to claim 1, characterized in that: The particle size of the modified γ phase ultrafine porous alumina is D50=0.5-0.7 μm, D90=1.2-1.5 μm, and the porosity of the modified γ phase ultrafine porous alumina is 20-40%.

3. The low-moisture and high-safety lithium battery separator according to claim 1, characterized in that: The method for obtaining modified γ-phase ultrafine porous alumina is as follows: gamma-phase ultrafine porous alumina, water and a silane coupling agent are mixed until uniform, dried and ground to obtain the modified γ-phase ultrafine porous alumina, wherein the ratio of gamma-phase ultrafine porous alumina, water and the silane coupling agent is (35-40): (50-70): (0.1-0.3) by mass.

4. The low-moisture and high-safety lithium battery separator according to claim 1, characterized in that: The coating thickness is 2 to 3 μm.

5. A method for preparing a low-moisture, high-safety lithium battery separator according to any one of claims 1 to 4, characterized in that: include: The slurry is coated on the base film and dried to obtain a coating on the base film to obtain a low-moisture and high-safety lithium battery separator. The slurry includes: water, modified γ-phase ultrafine porous alumina, an adhesive and a dispersant.

6. A slurry, characterized in that: include: The ratio of water, modified γ-phase ultrafine porous alumina, adhesive and dispersant is (50-70): (25-35): (5-8): (0.2-0.5) by mass.

7. The slurry according to claim 6, characterized in that The particle size of the slurry is D50: 0.4-0.6 microns, D90: 0.8-1.2 microns.

8. The method for preparing the slurry according to any one of claims 6 to 7, characterized in that: include: Water, modified γ-phase ultrafine porous alumina, adhesive and dispersant are mixed until uniform to obtain a slurry, wherein the ratio of water, modified γ-phase ultrafine porous alumina, adhesive and dispersant is (50-70): (25-35): (5-8): (0.2-0.5) by mass.

9. Application of silane coupling agent modified γ-phase ultrafine porous alumina in reducing the water content of diaphragms.

10. Application of silane coupling agent modified γ-phase ultrafine porous alumina in improving the ionic conductivity of the diaphragm.

Citation Information

Cited By

  • Porous alumina powder applied to lithium ion battery and preparation method of porous alumina powder

    CN119994068A